2017
DOI: 10.1021/jacs.7b00359
|View full text |Cite
|
Sign up to set email alerts
|

2,2′-Bipyridyl-Embedded Cycloparaphenylenes as a General Strategy To Investigate Nanohoop-Based Coordination Complexes

Abstract: Because of their unique cyclic architectures, tunable electronic properties, and supramolecular chemistries, cycloparaphenylenes (CPPs) have the potential to act as a new class of ligands for coordination cages, metal-organic frameworks, and small-molecule transition-metal complexes. However, currently there is no general strategy to coordinate the cyclic framework to a variety of metal centers. We report here a general and scalable synthetic strategy to embed 2,2'-bipyridine units into the backbone of CPPs. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 36 publications
(10 reference statements)
4
68
0
3
Order By: Relevance
“…Based on a Yamamoto coupling as the crucial ring‐closing step, Jasti and co‐workers succeeded in preparing a 2,2‐bipyridine‐embedded [8]CPP ( 17 ; Figure ) . The authors demonstrated that this compound coordinates to both Pd II and Ru II metal centres, and the resulting [Pd II [8]CPP Cl 2 ] ( 18 ), [Pd II ( [8]CPP ) 2 ](BF 4 ) 2 ( 19 ), and [Ru II [8]CPP (bpy) 2 ](PF 6 ) 2 complexes were characterized in solution and the solid state.…”
Section: Metal Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a Yamamoto coupling as the crucial ring‐closing step, Jasti and co‐workers succeeded in preparing a 2,2‐bipyridine‐embedded [8]CPP ( 17 ; Figure ) . The authors demonstrated that this compound coordinates to both Pd II and Ru II metal centres, and the resulting [Pd II [8]CPP Cl 2 ] ( 18 ), [Pd II ( [8]CPP ) 2 ](BF 4 ) 2 ( 19 ), and [Ru II [8]CPP (bpy) 2 ](PF 6 ) 2 complexes were characterized in solution and the solid state.…”
Section: Metal Coordinationmentioning
confidence: 99%
“…[102,103] Based on aY amamoto coupling as the crucial ring-closing step,J asti and co-workers succeeded in preparing a2 ,2bipyridine-embedded [8]CPP (17; Figure 11). [104] Theauthors demonstrated that this compound coordinates to both Pd II and Ru II metal centres,a nd the resulting [Pd II [8] (19), and [Ru II [8]CPP(bpy) 2 ]-(PF 6 ) 2 complexes were characterized in solution and the solid state.A lthough this new ligand class offers ar ather unique steric environment, to the best of our knowledge it has not yet been tested in transition-metal-catalyzed transformations.…”
Section: Metal Coordinationmentioning
confidence: 99%
“…Basierend auf einer Yamamoto‐Kupplung als entscheidendem Ringschlussschritt gelang es Jasti und Mitarbeitern, ein 2,2′‐Bipyridin‐eingebettetes [8]CPP ( 17 ; Abbildung ) herzustellen . Die Autoren zeigten, dass diese Verbindung sowohl an Pd II ‐ als auch an Ru II ‐Metallzentren koordiniert, und die daraus resultierenden [Pd II [8]CPP Cl 2 ]‐ ( 18 ), [Pd II ( [8]CPP ) 2 ](BF 4 ) 2 ‐ ( 19 ) und [Ru II [8]CPP (bpy) 2 ](PF 6 ) 2 ‐Komplexe wurden in Lösung und im Festkörper charakterisiert.…”
Section: Koordination An Metalleunclassified
“… Koordinationskomplexe von Übergangsmetallen mit Nanoreifen 18 (oben) und Festkörperstruktur des Pd‐Dimers 19 (unten), übernommen aus Lit. mit der Genehmigung der American Chemical Society, Copyright (2017).…”
Section: Koordination An Metalleunclassified
“…[10] Consequently, numerous well-ordered nanohoop structures have been designed and synthesized as host molecules for selective encapsulation or separation of specific fullerenes. [11][12][13][14][15][16][17][18][19][20][21][22] Not long ago, Miki and coworkers [23] successfully synthesized a twin nanoring of anthracene-containing [6] cycloparaphenyleneacetylene, and studied the corresponding nanohoop-fullerene (2C 60 ) host-guest complexes, which is the first example of 1:2 complexation between a π-conjugated hydrocarbon macrocyclic system and 2 fullerene molecules. More interestingly, Wang's group [24] developed a homoditopic molecular host, janusarene, which has 2 back-to-back compactly arranged nanocavities for guest complexation.…”
Section: Introductionmentioning
confidence: 99%